Analisis Kelayakan Tarif Berdasarkan Ability To Pay dan Willingness To Pay pada Bus Trans Jatim Koridor II - Ma'arif, M. Samsul; Utomo, Nugroho; Estikhamah, Fithri (Universitas Batanghari Jambi, 2025)
Transportation is one of the benchmarks in the economic development and development of a region. The government through the East Java Provincial Transportation Agency is developing public transportation in the form of the Trans Jatim Corridor II Bus transportation mode. However, in its operation, several problems were encountered, in general the load factor on corridor II is only 40 - 50%. This affects the low income of the Trans Jatim Bus. This study aims to determine the feasibility of fares based on the ability and willingness of passengers to pay for transportation. Primary data collection was obtained from interview surveys (questionnaires) on passengers. The data obtained were then analyzed using the ability to pay and willingness to pay approaches. The results of this study analysis obtained the amount of fares according to the ability to pay aspect for the general group is IDR 11,400 and for students is IDR 9,300. While the amount of fares according to the willingness to pay aspect for the general group is IDR 5,400 and for students is IDR 4,000. The ability and willingness of passengers to pay fares are above the current applicable rates. This shows that the current applicable rates can be increased on condition that facilities and services are improved.